2003
DOI: 10.1039/b212154a
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial natural products

Abstract: This review covers the literature published between January 1990 and December 2002 (inclusive) for natural products with reported antimycobacterial activity, with 248 citations to 352 compounds isolated from both terrestrial and marine sources The compounds are presented in order of chemical type, namely lipids/fatty acids and simple aromatics phenolics and acetogenic quinones, peptides, alkaloids, terpenes (monoterpenoids, diterpenes, sesquiterpenes, sesterterpenes and triterpenes) and steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(103 citation statements)
references
References 229 publications
(305 reference statements)
1
100
0
2
Order By: Relevance
“…Terpene quinones, including puupehenone metabolites, have been extensively studied for their antimicrobial and cytotoxic properties (32,(48)(49)(50)(51)(52). Nonetheless, this is the first report demonstrating that they selectively inhibit dormant drug-tolerant M. tuberculosis.…”
Section: Discussionmentioning
confidence: 95%
“…Terpene quinones, including puupehenone metabolites, have been extensively studied for their antimicrobial and cytotoxic properties (32,(48)(49)(50)(51)(52). Nonetheless, this is the first report demonstrating that they selectively inhibit dormant drug-tolerant M. tuberculosis.…”
Section: Discussionmentioning
confidence: 95%
“…According to Copp,20 secondary metabolites of terpenoid origin are among the most promising classes of natural products with antimycobacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent reports have demonstrated the in vitro bioassay activity of plant-derived terpenoids against M. tuberculosis (Cantrell et al, 2001;. The literature also reports the antimycobacterial activity of many classes of natural products: such as alkanes, phenolics, acetogenic quinines, flavonoids, triterpenes, flavonones and chalcones (Copp, 2003;Pavan et al, 2009). Previous results demonstrated that indigotin alkaloid can enhance macrophage functions and therefore contribute to the host defense against pathogens and tumors (Lopes et al, 2006).…”
Section: Plant With Antimycobacterial and Immunostimulating Activitymentioning
confidence: 99%